Synthesis, structure and magnetic properties of Y3Fe5-xAlxO12 garnets prepared by the soft chemical method - Silva Ortega, Pedro Paulo [UNESP]; Ramirez, Miguel Angel [UNESP]; Foschini, Cesar Renato [UNESP]; Garcia, Filiberto Gonzalez; Cilense, Mario [UNESP]; Simoes, Alexandre Zirpoli [UNESP] (Univ Novi Sad, Fac Technology, 2014)
A study was undertaken about the structural, morphological and magnetic properties at room temperature of crystalline aluminium substituted yttrium iron garnet, YIG (Y3Fe5-xAlxO12 with 1.5 < x < 1.7) nanoparticles prepared by polymeric precursor method at the temperature of 700 degrees C for 2 hours. The single-phase character and the well-defined structure of YIG nanoparticles were confirmed by X-ray diffraction, excluding the presence of any other phases. The Raman spectra showed that the changes of lattice vibration would influence interaction between the Fe ion and the host. Mean crystallite size of the single-phase powder was about 46-65 nm. Particles' morphology was investigated by high-resolution transmission electron microscopy, which shows that the particles were agglomerated. From hysteresis loops, particles' efficiency range from 91.4% to 95.9% as Fe/Al ratio decreases. Saturation magnetization was affected by the particle size and Fe/Al stoichiometric ratio. We observe that the saturation magnetization increases as the Fe/Al ratio is raised due to enhancement of the surface spin effects.
Keywords: yttrium iron garnet; powder; chemical synthesis; characterization; magnetic properties